Size resolved aerosol respiratory doses in a Mediterranean urban area: From PM10 to ultrafine particles. (August 2020) - Manigrasso, Maurizio; Costabile, Francesca; Liberto, Luca Di; Gobbi, Gian Paolo; Gualtieri, Maurizio; Zanini, Gabriele; Avino, Pasquale
Graphical abstract: Highlights: Mass doses may be dominated by coarse aerosol deriving from natural sources. Number and surface area, rather than mass, are controlled by combustion aerosols. The highest combustion aerosol doses coincide with highest oxidative activities. The dose deposited on the olfactory bulb is mainly made of combustion UFPs. Neurodegenerative diseases should be associated to number and surface area metrics. Abstract: In the framework of the 2017 "carbonaceous aerosol in Rome and Environs" (CARE) experiment, particle number size distributions have been continuously measured on February 2017 in downtown Rome. These data have been used to estimate, through MPPD model, size and time resolved particle mass, surface area and number doses deposited into the respiratory system. Dosimetry estimates are presented for PM10, PM2.5, PM1 and Ultrafine Particles (UFPs), in relation to the aerosol sources peculiar to the Mediterranean basin and to the atmospheric conditions. Particular emphasis is focused on UFPs and their fraction deposited on the olfactory bulb, in view of their possible translocation to the brain. The site of PM10 deposition within the respiratory system considerably changes, depending on the aerosol sources and then on its different size distributions. On making associations between health endpoints and aerosol mass concentrations, the relevant coarse and fine fractions would be more properly adopted, because they have different sources, different capability of penetrating deep into the respiratory system and different toxicological implications. The separation between them should be set at 1 µm, rather than at 2.5 µm, because the fine fraction is considerably less affected by the contribution of the natural sources. Mass dose is a suitable metric to describe coarse aerosol events but gives a poor representation of combustion aerosol. This fraction of particles, made of UFPs and of accumulation mode particles (mainly with size below 0.2 µm), is of high health relevance. It elicited the highest oxidative activity in the CARE experiment and is properly described by the particle surface area and by the number metrics. Such metrics are even more relevant for the UFP doses deposited on the olfactory bulb, in consideration of the role recognized to oxidative stress in the progression of neurodegenerative diseases. Such metrics would be more appropriate, rather than PMx mass concentrations, to correlate neurodegenerative pathologies with aerosol pollution.